2011
DOI: 10.20537/vm110211
|View full text |Cite
|
Sign up to set email alerts
|

The electronic atlas of bifurcation diagrams of the Kowalevski–Yehia gyrostat

Abstract: Рассматривается интегрируемый случай Ковалевской-Яхья в динамике гиростата. Представлен новый подход к классификации бифуркационных диаграмм приведенных систем. Получены конструктивно проверяемые условия существования критических движений на сечении фиксированной постоянной площадей поверхностей, несущих бифуркационную диаграмму трех интегралов полной исходной си-стемы. Случаи, когда эти условия претерпевают качественные перестройки, дают аналитические зави-симости между постоянной площадей и величиной гироста… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
0
8
0
Order By: Relevance
“…The transformations of the diagram for λ > 0 take place at the following values of the parameter: λ * , 1 , λ * , √ 2 . The study of intersections of the curves δ 2 , ∆ 0 gives, in addition to the values found in [3], the separating value λ = 1 . All types of the diagram of the subsystem M 1 are shown in Fig.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…The transformations of the diagram for λ > 0 take place at the following values of the parameter: λ * , 1 , λ * , √ 2 . The study of intersections of the curves δ 2 , ∆ 0 gives, in addition to the values found in [3], the separating value λ = 1 . All types of the diagram of the subsystem M 1 are shown in Fig.…”
Section: Introductionmentioning
confidence: 84%
“…In particular, taking into account the MATHEMATICS 2011. Issue 4 existence conditions for critical motions found in [4,3], for the integral constants s, ℓ, h we get…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations